Tim4‐Functionalized HBEV‐Chip by Isolating Plasma‐Derived Phosphatidylserine‐Positive Small Extracellular Vesicles for Pan‐Cancer Screening. Issue 7 (31st December 2021) - Yang, Liu; Tong, Xuedong; Zhang, Yong; Li, Yan; Liu, Jiangwei; Yin, Ruiling; Zeng, Dong; Yuan, Yue; Deng, Kun
Abstract: Thanks to containing tumor‐related molecules, small extracellular vesicles (sEVs) are emerging as biomarkers in tumor liquid biopsy and commonly employed to diagnose a specific cancer. However, a pan‐cancer screening method for pre‐symptomatic patients is crucial to achieving the early cancer detection. Herein, a lipid‐protein capture system on herringbone (HB) microfluidic chip ( HB EV‐Chips) to isolate multiple tumor‐derived sEVs is constructed. Phosphatidylserine (PS) is abnormally surface‐supposed on tumor‐derived sEVs and binds T‐cell immunoglobulin domain and mucin domain‐containing protein 4 (Tim4) in calcium‐dependent manner. PS + sEVs isolated by the HB EV‐Chips is perform on liquid chromatography electrospray ionization tandem mass spectrometry and it is found that PS + sEVs are highly correlated with tumor‐related pathway ( P < 0.05), such as Cdc42 protein signal transduction, neuropilin signaling pathway, and Wnt signaling pathway. And it is further validated in clinical sample and found that PS + sEV number shows statistical difference between cancer patients and healthy donors in plasma ( P < 0.01) and has efficient diagnostic power (area under curve = 0.86), suggesting PS + sEV as potential biomarker for pan‐cancer screening. The Tim‐4 functionalized device facilitates the early multiple cancer detection, providing the potential to be used as a rapid‐screening tool in clinical setting. Abstract : 125 ng mL −1 functionalized Tim4 and corresponding eluent of 20 × 10 −3 m ethylene diamine tetraacetic acid successfully construct the HB EV‐Chip for PS + small extracellular vesicles (sEVs) isolation in 200 µL clinical plasma. And it has highest purity among ultracentrifugation, precipitation, and size exclusion chromatography. For PS + sEVs analysis, its count shows difference between plasma of pan‐cancers and health ( P < 0.01) and its area under curve was 0.86 as a pan‐cancer screening marker.